Laparoscopic two-stage hepatectomy for bilobar colorectal liver metastases. Issue 13 (22nd September 2015) - Fuks, D; Nomi, T; Ogiso, S; Gelli, M; Velayutham, V; Conrad, C; Louvet, C; Gayet, B
Abstract: Background: Despite the gradual diffusion of laparoscopic liver resection, the feasibility and results of laparoscopic two-stage hepatectomy (TSH) for bilobar colorectal liver metastases (CRLM) have not been described frequently. This study aimed to evaluate the feasibility, safety and oncological outcomes of laparoscopic TSH for bilobar CRLM. Methods: All patients eligible for laparoscopic TSH among those treated for bilobar CRLM from 2000 to 2013 were included. Demographics, tumour characteristics, surgical procedures, and short- and long-term outcomes were analysed. Results: Laparoscopic TSH was planned in 34 patients with bilobar CRLM, representing 17·2 per cent of all 198 patients treated for bilobar CRLM. Thirty patients received preoperative chemotherapy, and 20 had portal vein occlusion to increase the volume of the remnant liver. Laparoscopic resection of the primary colorectal tumour was integrated within the first-stage hepatectomy in 11 patients. After a median interval of 3·1 months, 26 patients subsequently had a successful laparoscopic second-stage hepatectomy, including 18 laparoscopic right or extended right hepatectomies. The mortality rate for both stages was 3 per cent (1 of 34), and the overall morbidity rate for the first and second stages was 50 per cent (17 of 34) and 54 per cent (14 of 26) respectively. Mean length of hospital stay was 6·1 and 9·0 days respectively. With a median follow-up of 37·8 (range 6–129) months, 3- and 5-year overall survival rates in patients who completed TSH were 78 and 41 per cent respectively. The 3- and 5-year disease-free survival rates were 26 and 13 per cent respectively. Conclusion: Laparoscopic TSH for bilobar CRLM is safe and does not jeopardize long-term outcomes in selected patients. Abstract : For expert centres